Patent Ethics: The Misalignment of Views Between the Patent System and the Wider Society - Forsberg, Ellen-Marie; Hanssen, Anders Braarud; Nielsen, Hanne Marie; Olesen, Ingrid (Science and engineering ethics, 2018)
Concerns have been voiced about the ethical implications of patenting practices in the field of biotechnology. Some of these have also been incorporated into regulation, such as the European Commission Directive 98/44 on the legal protection of biotechnological inventions. However, the incorporation of ethically based restrictions into patent legislation has not had the effect of satisfying all concerns. In this article, we will systematically compare the richness of ethical concerns surrounding biotech patenting, with the limited scope of ethical concerns actually addressed in the patent system. As sources of our analyses we will use literature and document studies and a survey with important stakeholders and experts related to Norwegian patenting in the aquacultural biotechnology sector. We will structure the analyses with an ethical matrix, developed for this purpose. Showing the misalignment of the discussions within and outside the patent system, we suggest that an important reason for the ethical controversy still surrounding patenting is that ethical questions keep being framed in a narrow way within the system. Until a richer set of ethical considerations is addressed head-on within the patent system, the patent system will continue to evoke academic and interest group criticism, potentially contributing to a legitimacy crisis of the whole system.